Associations between manure pumping out of the site and exposure to nearby manure applications with the incidence of porcine reproductive and respiratory syndrome virus and porcine epidemic diarrhea virus outbreaks in wean-to-market pig populations in the Midwestern United States - Serafini Poeta Silva, Ana Paula; Amorim Moura, Cesar; Johansen, Nicholas; Moraes, Daniel; Romero Nicolino, Rafael; Magalhães, Edison Sousa; Rupasinghe, Kinath; Jayaraman, Swaminathan; Rademacher, Christopher; Trevisan, Giovani; Linhares, Daniel C. L.; Silva, Gustavo S. (Frontiers in Veterinary Science, 2025)
IntroductionManure handling is an integral part of swine production, providing valuable nutrients for crop fields but also posing potential biosecurity risks. This study investigated the association between manure removal and nearby manure applications with the occurrence of porcine reproductive and respiratory syndrome virus (PRRSV) and porcine epidemic diarrhea virus (PEDV) outbreaks in wean-to-market pig lots.MethodsData from a swine production system were analyzed for the period between July 2020 and December 2022 using a matched case–control design. Cases were defined as PRRSV or PEDV outbreaks confirmed through veterinary assessment and pathogen RNA detection. Manure exposure was assessed at the site level, including (1) pumping manure out from the site and (2) proximity (≤1.61, 4.82, and 8.04 km) to fields receiving manure. Conditional logistic regression models evaluated outbreak odds ratios within 5 weeks of exposure. Additional mixed effects models identified risk factors associated with PRRSV outbreaks.ResultsAmong 2,592 wean-to-market lots across 599 sites, 1,370 lots had at least one manure pumping event, 380 PRRSV outbreaks, and 103 PEDV outbreaks. PRRSV outbreaks were significantly associated (p-value < 0.05) with manure pumping (Odds Ratio [OR] = 3.38, 95% CI: 1.86–6.11) and proximity to fields receiving manure at distances of ≤1.61 km (OR = 4.09, 95% CI: 1.05–16.00) and 4.82 km (OR = 3.05, 95% CI: 1.12–8.27). Significant risk factors for PRRSV outbreaks after manure pumping included herd size (>10,000 pigs: OR = 6.75, 95% CI: 3.24–14.06), week of pumping (1st–4th week post-placement: OR = 5.64, 95% CI: 1.76–18.08), and prior PRRSV-positive lots (OR = 3.52, 95% CI: 1.55–7.97). PRRSV outbreaks following manure exposure from adjacent fields were more likely in large herds (>10,000 pigs: OR = 11.47, 95% CI: 3.43–44.52) and at closer distances <1.61 km (OR = 11.3, 95% CI: 2.73–53.43). No significant associations were found between PEDV outbreaks and manure exposure, likely due to the limited observations in this study.DiscussionThese findings highlight the significance of manure management in PRRSV transmission risk, particularly the timing of manure pumping, herd size, and proximity to manure-applied fields. Improving biosecurity measures during manure handling can help lower PRRSV transmission risks in swine production.